A review of the applications of artificial intelligence and big data to buildings for energy-efficiency and a comfortable indoor living environment - Mehmood, Muhammad Uzair; Chun, Daye; Zeeshan; Han, Hyunjoo; Jeon, Gyuyeob; Chen, Kuan (Energy and Buildings, 2019)
After decades of evolution and improvements, Artificial Intelligence (AI) is now taking root in our daily lives, and is starting to profoundly influence the fields of architecture and sustainability. The applications of AI to sustainable architecture include energy-efficient building design, forecasting and minimizing energy consumption, strategizing for mitigating impacts on environment and climate, and enhancements in the safety and comfort of the living environment. Due to the significant increases in internet speed and accessibility and the drops in computer prices and data storage costs in recent years, Big Data (BD) nowadays plays an important supplementary role to AI. Algorithms and computer codes have been developed for data mining and analysis. BD rejuvenates AI methods and applications in many areas, including sustainable architecture. The present paper starts with an introduction to AI history and techniques. This is followed by a discussion on how AI and BD can be used to design and operate energy–efficient commercial buildings and residential houses, followed by a review of recent applications of AI and BD to energy-efficient buildings with an emphasis on the use of machine learning (ML) and large databases. Future research topics are suggested at the end of this paper. It is reemphasized in the present paper that AI, when combined with BD, can tremendously increase the energy efficiency and cost effectiveness of buildings which are designed to provide occupants with a comfortable indoor living environment.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2019.109383 5072953:BLM2GXIE openalex: W2969536608
Keywords: Artificial intelligence; Big data; Green buildings; Sustainable architecture; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11954 Energy Efficiency in Manufacturing and Industry Sector; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes

Retrofitting measures for climate resilience: Enhancing the solar performance of Malaysian school buildings with passive design concepts - Alwi, Najah Md; Flor, J-F; Anuar, Nur Hidayah Khairul; Mohamad, J; Hanafi, N N H; Muhammad, N H; Zain, M H K M; Nasir, M R M (IOP Conference Series: Earth and Environmental Science, 2022)
Climate-sensitive school buildings can enhance students’ learning performance and reduce the building’s overall energy consumption. This paper reports on a post-occupancy study of contemporary school buildings in Malaysia, assessing problems of solar heat gain. The research aims to propose retrofitting measures based on passive design principles adapted specifically for the Malaysian tropical climate to strengthen the resilience of local school buildings in a global climate emergency. On-site measurements in two different schools provided the empirical basis for the design modifications. The monitoring procedure included site observations, extended temperature and humidity measurements, and daylight analysis. A virtual classroom model was generated based on the on-site measurements, and a parametric simulation study was conducted to evaluate the proposed retrofit measures’ effectiveness. The model variables were evaluated and compared to identify the passive design elements that significantly impact heat gains and thermal comfort. The results showed that increasing roof overhangs to 1500 mm for additional shading, sensitive selection of roof materials and colours of white-painted zinc roof, and reduction of window-to-wall ratio by 30% to the operable windows helps to reduce solar gains by 6% to improve comfort conditions within the classrooms. Overall, the study provided evidence of how passive solar building design would benefit the climate resilience of Malaysian schools.
openalex: W4310789718
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate resilience; oa:keyword:malaysian school buildings; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes